PENGARUH INDIKATOR NONKEUANGAN DAN KEUANGAN TERHADAP KINERJA PERUSAHAAN (KOMPARASI EMPIRIS: INDONESIA, VIETNAM, DAN MALAYSIA) - Didi Achjari; Sri Suryaningsum (Jurnal Ekonomi Dan Bisnis, 2015)
The effect of indicators non-financial and financial Implementation has been interesting topics in Indonesia,Malaysia, and Vietnam. The current study aims to investigate transparation of indicators non-financial andfinancial especially in telecommunication and technology industry sector. The indicators of non-financial are measured using some surrogates such as corporate action, GCG elements inorganization structure, Bureau van Dijk Electronic Publishing (BvDEP) independence indicator, and auditedfinancial report result. The indicator of financial is measured using one surrogate as return of total assets. Samples used in this studyare telecommuncation and technology companies from three countries are Indonesia, Malaysia, and Vietnam.Data obtained from OSIRIS database from year 2005 to 2007 is examined using regression analysis. This study result is factors that influence net profit in Indonesia, Malaysia, and Vietnam are vary. In Indonesia,independence indicator and corporate action affect net profit. In Malaysia, the influencing factors are corporateaction, independence indicator, financial report result, and return of total assets. Meanwhile, in Vietnam,corporate actions, the number of GCG members and return of total assests influence the net profit oftelecommunication and technology companies.Keywords: indicators of financial & non-financial, telecommunication and technology industry, Indonesia, Vietnam, Malaysia.